A fully replication-competent adenovirus vector with enhanced oncolytic properties - Toth, K (2010)
We have studied the oncolytic efficacy of two adenovirus vectors named KD3 and INGN 007, which differ from each other only in that whereas KD3 has two small deletions in its e1a gene that restrict its replication to rapidly cycling cells, INGN 007 has wild-type e1a gene. Both vectors overexpress the adenovirus death protein (ADP). Both KD3 and INGN 007 effectively suppressed the growth of subcutaneous human A549 and Hep3B tumors in nude mice upon intratumoral injection, and contained the growth of subcutaneous LNCaP tumors after intravenous injection, making some tumors shrink or disappear. However, in a more demanding model, intravenous injections of neither KD3 nor wild-type Ad5 were effective against subcutaneous A549 tumors, whereas INGN 007 increased the mean survival time by 35%. INGN 007 was also effective in suppressing tumor growth in a challenging A549 orthotopic lung cancer model. INGN 007 was superior to dl1520 (ONYX-015) in repressing subcutaneous A549 tumors. Our results suggest that vectors such as INGN 007 might provide better antitumor efficacy in the clinic as well.